Companion robots to mitigate loneliness among older adults: Perceptions of benefit and possible deception - Berridge, Clara; Zhou, Yuanjin; Robillard, Julie M.; Kaye, Jeffrey (Frontiers in Psychology, 2023)
Objective: Objective: Given growing interest in companion robots to mitigate loneliness, large-scale studies are needed to understand peoples’ perspectives on the use of robots to combat loneliness and attendant ethical issues. This study examines opinions about artificial companion (AC) robots regarding deception with dementia and impact on loneliness. Methods: Data are from a survey of 825 members of the [BLINDED] cohort (response rate=45%). Sixty percent (n=496) of the age diverse sample (range=25-88; m=64; SD=13.17) is over 64, allowing us to compare across age and consider current and future older adults. Ordinal logistic regressions examined relationships between age, health, and other socio-demographic characteristics and perceptions of impact on loneliness and comfort with deception. Results: Most participants (68.7%) did not think an AC robot would make them feel less lonely and felt somewhat-to-very uncomfortable (69.3%) with the idea of being allowed to believe that an artificial companion is human. In adjusted models, one additional year of age was associated with lower likelihood of perceived benefit of reducing loneliness (Odds Ratio [OR]=0.98; [0.97-0.99], p=.003) and lower comfort with deception (OR=0.99; [0.97-1.00], p=.044). Being female was associated with lower likelihood of comfort with deception (OR=0.68; [0.50-0.93], p=.014) and high confidence using computers with greater comfort (OR=2.18; [1.42-3.38], p<.001). Discussion: There was not strong support for AC robots to mitigate loneliness. Most participants were uncomfortable with this form of deception, indicating need for design solutions for those who want to avoid this possibility, as well as greater attentiveness to desirability and comfort across age and gender.